Innovative methods to analyse the impact of gender norms on adolescent health using global health survey data. (January 2022) - Cislaghi, Beniamino; Weber, Ann M.; Shakya, Holly B.; Abdalla, Safa; Bhatia, Amiya; Domingue, Benjamin W.; Mejía-Guevara, Iván; Stark, Lindsay; Seff, Ilana; Richter, Linda M.; Baptista Menezes, Ana Maria; Victora, Cesar G.; et al.
Abstract: Background: Understanding how gender norms affect health is an important entry point into designing programs and policies to change norms and improve gender equality and health. However, it is rare for global health datasets to include questions on gender norms, especially questions that go beyond measuring gender-related attitudes, thus limiting gender analysis. Methods: We developed five case studies using health survey data from six countries to demonstrate approaches to defining and operationalising proxy measures and analytic approaches to investigating how gender norms can affect health. Key findings, strengths and limitations of our norms proxies and methodological choices are summarised. Findings: Case studies revealed links between gender norms and multiple adolescent health outcomes. Proxys for norms were derived from data on attitudes, beliefs, and behaviours, as well as differences between attitudes and behaviours. Data were cross-sectional, longitudinal, census- and social network-based. Analytic methods were diverse. We found that gender norms affect: 1) Intimate partner violence in Nigeria; 2) Unhealthy weight control behaviours in Brazil and South Africa; 3) HIV status in Zambia; 4) Health and social mobility in the US; and 5) Childbirth in Honduras. Interpretation: Researchers can use existing global health survey data to examine pathways through which gender norms affect health by generating proxies for gender norms. While direct measures of gender norms can greatly improve the understanding of how gender affects health, proxy measures for norms can be designed for the specific health-related outcome and normative context, for instance by either aggregating behaviours or attitudes or quantifying the difference (dissonance) between them. These norm proxies enable evaluations of the influence of gender norms on health and insights into possible reference groups and sanctions for non-compliers, thus informing programmes and policies to shape norms and improve health. Highlights: This article presents effective methods to study gender norms in existing global health survey data. We devised conceptual pathways linking gender norms to gender-based health disparities. We identified gender norms proxies and reference groups enforcing the norm. We tested hypotheses linking gender norms to health. These methods can aid policy and programme design to advance gender equality and health.